An adaptive congestion control algorithm. (4th July 2021) - Gupta, Ajay Kumar; Singh, Devendra; Singh, Karan; Verma, Lal Pratap
Abstract: The congestion of the network increases exponentially due to continuous growth of the Internet. TCP is a protocol of Transport layer which deals with the congestion of the network. TCP has many variants to deal with different types of congestion problems. Congestion of the network depends on many factors like transfer of packet size, type of cross traffic, number of competing connections, the load on every link in the path, router buffer size and bottleneck queue size. This paper presents a new congestion detection method which is based on bottleneck queue size. It is estimated according to variation of round-trip time. The experimental results confirm that the proposed TCP provide better results for throughput and packet drops.